1984
DOI: 10.1159/000466258
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Human Albumin by Caprylate and Acetyltryptophanate

Abstract: The thermal stabilization of human albumin by caprylate (CA) and acetyltryptophanate (AT) was studied by monitoring the formation of albumin polymer (defined as species larger than dimer) on the basis of its molecular size as well as its characteristic migration as α-globulin. Heating 5% protein solutions of purified albumin monomer, Cohn fraction V, and fraction IV-4 + V at 60°C in 0.1 M sodium phosphate or 145 mM sodium chloride, pH 7.0, established the following order of stabilizer effectiveness: 4 mM CA + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In addition to coming from the ischemic gut, NEFA may be released by burn injuries, bone fractures, or be administered with resuscitation (8–10). Pharmaceutical albumin is stabilized for heat sterilization by adding approximately 10 times the physiologic concentration of NEFA (11,12). In vitro , we showed that at these concentrations and at concentrations measured in shock, NEFA in the presence of blood cells detaches from albumin, disrupts cell membranes, and induces hemolysis (11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to coming from the ischemic gut, NEFA may be released by burn injuries, bone fractures, or be administered with resuscitation (8–10). Pharmaceutical albumin is stabilized for heat sterilization by adding approximately 10 times the physiologic concentration of NEFA (11,12). In vitro , we showed that at these concentrations and at concentrations measured in shock, NEFA in the presence of blood cells detaches from albumin, disrupts cell membranes, and induces hemolysis (11).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic use of human serum albumin (HSA) is recommended in the treatment of complications of liver cirrhosis, such as hepatorenal syndrome, or after paracentesis (1)(2)(3). Pharmaceutical-grade albumin preparations contain a high amount of medium fatty acid octanoate and tryptophan as stabilizers, which are a prerequisite for virus inactivation and the avoidance of macromolecule formation during the preparation process (4)(5)(6). Content of those stabilizers in pharmaceutical-grade HSA preparations are several times higher than albumin concentration, up to a molar ratio of 5.4 mol/mol (7,8).…”
mentioning
confidence: 99%